Predictive capacity of a genetic risk score for coronary artery disease in assessing recurrences and cardiovascular mortality among patients with myocardial infarction - Rincón, Luis Miguel; Subirana, Isaac; Pérez del Villar, Candelas; Sánchez, Pedro L.; Zamorano, José Luis; Marrugat, Jaume; Elosua, Roberto (Frontiers in Cardiovascular Medicine, 2023)
Aim This study aimed to evaluate the capacity of a genetic risk score (GRS) for coronary artery disease (CAD) independent of classical cardiovascular risk factors to assess the risk of recurrence in patients with first myocardial infarction. The secondary aim was to determine the predictive value of this GRS. Methods We performed a meta-analysis of individual data from three studies, namely, a prospective study including 75 patients aged <55 years, a prospective study including 184 patients with a mean age of 60.5 years, and a case–control study (77 cases and 160 controls) nested in a cohort of patients with first myocardial infarction. A GRS including 12 CAD genetic variants independent of classical cardiovascular risk factors was developed. The outcome was a composite of cardiovascular mortality and recurrent acute coronary syndrome. Results The GRS was associated with a higher risk of recurrence [hazard ratio = 1.24; 95% confidence interval (CI): 1.04–1.47]. The inclusion of the GRS in the clinical model did not increase the model’s discriminative capacity (change in C-statistic/area under the curve: 0.009; 95% CI: −0.007 to 0.025) but improved its reclassification (continuous net reclassification index: 0.29; 95% CI: 0.08–0.51). Conclusion The GRS for CAD, independent of classical cardiovascular risk factors, was associated with a higher risk of recurrence in patients with first myocardial infarction. The predictive capacity of this GRS identified a subgroup of high-risk patients who could benefit from intensive preventive strategies.